Progress and applications of quantum precision measurement based on SERF effect - Zhai, Yueyang; Yue, Ziqian; Li, Lin; Liu, Ying (Frontiers in Physics, 2022)
With the development of quantum precision measurement technology, measurement methods based on magnetic, optical and atomic interactions have started to receive widespread attention. Among them, quantum precision measurement based on the spin-exchange relaxation-free (SERF) effect shows great potential by its ultra-high measurement sensitivity. This paper introduces the basic working principles of the magnetic field and inertia measurement based on the SERF effect, and focuses on the research progress and applications of SERF quantum precision measurement in fundamental physics, inertial navigation and biomedicine. Finally, we propose a prospect for the directions of SERF quantum precision measurement.